TiO2/CuO/Cu2O Photovoltaic Nanostructures Prepared by DC Reactive Magnetron Sputtering - Grzegorz Wisz; Paulina Sawicka-Chudy; Maciej Sibiński; Dariusz Płoch; Mariusz Bester; Marian Cholewa; Janusz Woźny; Rostyslav Yavorskyi; Lyubomyr Nykyruy; Marta Ruszała (Nanomaterials, 2022)
In this study, titanium dioxide/copper oxide thin-film solar cells were prepared using the reactive direct-current magnetron sputtering technique. The influence of the deposition time of the top Cu contact layer on the structural and electrical properties of photovoltaic devices was analyzed. The structural and morphological characterization of the TiO2/CuO/Cu2O solar cells was fully studied using X-ray diffraction (XRD), scanning electron microscopy (SEM), and current–voltage (I-V) characteristics. Additionally, using van der Pauw sample geometries, the electrical properties of the titanium dioxide and copper oxide layers were investigated. From the XRD study, solar cells were observed in cubic (Cu2O), monoclinic (CuO), and Ti3O5 phases. In addition, the crystallite size and dislocation density for copper oxide layers were calculated. Basic morphological parameters (thickness, mechanism of growth, and composition of elements) were analyzed via scanning electron microscopy. The thicknesses of the titanium dioxide and copper oxide layers were in the range of 43–55 nm and 806–1223 nm, respectively. Furthermore, the mechanism of growth and the basic composition of the elements of layers were analyzed. The I-V characteristic curve confirms the photovoltaic behavior of two titanium dioxide/copper oxide thin-film structures. The values of short-circuit current density (Jsc) and open-circuit voltage (Voc) of the solar cells were: 4.0 ± 0.8 µA/cm2, 16.0 ± 4.8 mV and 0.43 ± 0.61 µA/cm2, 0.54 ± 0.31 mV, respectively. In addition, the authors presented the values of Isc, Pmax, FF, and Rsh. Finally, the resistivity, carrier concentration, and mobility are reported for selected layers with values reflecting the current literature.